Neuropathic pain and temporal expression of preprodynorphin, protein kinase C and N-methyl-D-aspartate receptor subunits after spinal cord injury - Labombarda, Maria Florencia (2008)
Central neuropathic pain is refractory to conventional treatment and thus remains a therapeutic challenge. In this work, we used a well-recognized model of central neuropathic pain to evaluate time-dependent expression of preprodynorphin (ppD), protein kinase C gamma (PKCgamma) and NMDA receptor (NMDAR) subunits NR1, NR2A and NR2B, all critical players in nociceptive processing at the spinal level. Male Sprague-Dawley rats were subjected to spinal hemisection at T13 level and sham-operated rats were included as control animals. The development of hindpaw mechanical allodynia was assessed using the von Frey filaments test. Real time RT-PCR was employed to determine the relative mRNA levels of NMDAR subunits, ppD and PKCgamma in the dorsal spinal cord 1, 14 and 28 days after injury. Our results show that, coincident with the allodynic phase after injury, there was a strong up-regulation of the mRNAs coding for ppD, PKCgamma and NMDAR subunits in the dorsal spinal cord caudal to the injury site. The present study provides further evidence that these molecules are involved in the development/maintenance of central neuropathic pain and thus could be the target of therapeutic approaches.